Books in Riga Sent by Martin Ludwig Rhesa to Abraham Jakob Penzel - Kazakėnaitė, Ernesta (Knygotyra, 2019)
Martin Ludwig Rhesa sent Lithuanian books to Abraham Jakob Penzel in Jena twice: in May 1818 and in the spring of 1819. Although this is a well-known fact, there is a lack of knowledge concerning which and how many books were in those two packages. Rhesa himself, in a letter to Scheffner dated April 1819, mentioned the following three books from the second package:Martin Ludwig Rhesa sent Lithuanian books to Abraham Jakob Penzel in Jena twice: in May 1818 and in the spring of 1819. Although this is a well-known fact, there is a lack of knowledge concerning which and how many books were in those two packages. Rhesa himself, in a letter to Scheffner dated April 1819, mentioned the following three books from the second package:1) A new edition of the Lithuanian Bible published by Rhesa (1816);2) Gottfried Ostermeyer’s Erste Littauische Liedergeschichte (1793);3) Gotthard Friedrich Stender’s Neue vollständigere Lettische Grammatik, Nebst einem hinlänglichen Lexico.But it is a mere drop in the ocean, as it is known that Rhesa not only bought books for this occasion, but also added 12 books from his own book collection, and a bundle from Ostermeyer.We also know little about the content of the first package sent to Penzel in May 1819. There are few books in the Latvian Academic Library that have inscriptions with the name Penzel in them. As it is clear from the published copies of the inscriptions (see pictures in this paper), in all of those, Rhesa is mentioned as a sender – all except for one book without any coherent record, which this paper concludes is also one of the books sent by Rhesa. This paper concludes that the following is the list of the books from 1818 (the first three in the list were noticed years ago by Tumelis and Jovaišas): 1) May 29, 1818 Christian Daniel Hassenstein Nuſidawimai βwento Karawimo (1814) (LU AB sign: D6 5813); 2) May 31, 1818 Nathaniel Friedrich Ostermeyer Graudenimo balsas (1818) (LU AB sign: D6 5787); 3) June 1, 1818 Nathaniel Friedrich Ostermeyer Nedel=Dienos knygeles, krikſʒ́ćʒoniems ſuraβytos (1818), (LU AB sign: D6 5517); 4) June 2, 1818 Adam Friedrich Schimmelpfennig Iß naujo pérveiʒdėtos ir pagérintos giesmiû=Knygos (1791), kartu su Danielio Kleino Naujos labbay priwalingos ir Dußoms naudingos Maldû Knygélos (LU AB sign: D6 5515); 5) (without a provenance of Penzel himself) Christian Daniel Hassenstein Kaip krikßcʒonißzka Wiera bey Baznycʒia, Ʒmonû pagadinta (1818) (LU AB sign: D6 5518); 6) (supposedly) Christian Donaleitis Das Jahr in Vier Gesängen: Ein Ländliches Epos (1818).